3D Imaging for Safety and Security - Koschan, Andreas; Pollefeys, Marc.; Abidi, Mongi; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
The past decades have seen significant improvements in 3D imaging where the related techniques and technologies have advanced to a mature state. These exciting developments have sparked increasing interest in industry and academia in the challenges and opportunities afforded by 3D sensing. As a consequence, the emerging area of safety and security related imaging incorporates these important new technologies beyond the limitations of 2D image processing. This book is so far the first that covers the current state of the art in 3D imaging for safety and security. It reports about selected contributions given at the (3z(BWorkshop on Advanced 3D Imaging for Safety and Security(3y (Bheld in conjunction with the International Conference on Computer Vision and Pattern Recognition CVPR 2005, June 2005, San Diego, CA. The workshop brought together pioneering academic and industrial researchers in the field of computer vision and image analysis. Special attention was given to advanced 3D imaging technologies in the context of safety and security applications. Comparative evaluation studies showing advantages of 3D imaging over traditional 2D imaging for a given computer vision or pattern recognition task were emphasized. Moreover, additional experts in the field of 3D imaging for safety and security were invited by the editors for a contribution to this book. The book is structured into two parts, each containing five or six chapters on (1) Biometrics and (2) Safety and Security Applications.s
Biometrics -- 3D Assisted Face Recognition: A Survey -- A Survey on 3D Modeling of Human Faces for Face Recognition -- Automatic 3D Face Registration Without Initialization -- A Genetic Algorithm Based Approach for 3D Face Recognition -- Story of Cinderella -- Human Ear Detection From 3D Side Face Range Images -- Safety and Security Applications -- Synthetic Aperture Focusing Using Dense Camera Arrays -- Dynamic Pushbroom Stereo Vision -- 3D Modeling of Indoor Environments -- 3D Site Modelling and Verification -- Under Vehicle Inspection with 3d Imaging.
Keywords: Computer science; Computer science -- Mathematics; Computer graphics; Image processing; Pattern recognition; Computer Science; Computer Graphics; Pattern Recognition; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Math Applications in Computer Science; Electronic books